Residual stresses in cold-formed steel sections: An overview of influences and measurement techniques - Mutafi, Ayad; Irwan, J. M.; Yidris, Noorfaizal; Alshalif, Abdullah Faisal; Saif, Yazid; Abdulrahman, Hamdi; Mutaafi, Ala; Al-Ashmori, Yasser Yahya; Amran, Mugahed; Maureira-Carsalade, Nelson; Avudaiappan, Siva (Elsevier, 2025)
Cold-formed steel (CFS) members offer significant advantages over hot-rolled sections, primarily due to their high strength-to-weight ratio and versatility in forming various cross-sectional shapes. These attributes make CFS an efficient choice for design and construction. This paper reviews current design methods for CFS, focusing on the impact of initial imperfections. It also examines various techniques for measuring residual stress in CFS sections, including analytical, experimental, and numerical approaches. The study concludes that while analytical methods are effective, they become complex when accounting for material anisotropy. Laboratory techniques provide reliable measurements but are limited in detecting through-thickness residual stresses. Numerical approaches offer comprehensive insights but require further validation across different material and geometric configurations. The paper highlights the need for advanced analytical models, improved laboratory methods, and expanded numerical techniques to address existing knowledge gaps in residual stress assessment for CFS structures.